International social work research issues and prospects - Tripodi, Tony.; Potocky-Tripodi, Miriam (Oxford : Oxford University Press, 2007)
The authors establish three discrete varieties of research - supra-national, intra-national, and trans-national, and explores issues and examples within each. The format of this work helps readers learn how to define and distinguish each kind of research, then provides examples of applications of the three.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research -- Cross-cultural studies; Social service -- Research -- International cooperation